Families in Converging Europe - Oinonen, E. author. aut Link
XIV, 212 p.
Keywords: This book examines common familial trends and differences throughout Europe from the 1960s onwards and discusses the most common theoretical explanations for convergence and divergence. Eriikka Oinonen reveals how structural factors such as the labour market, the welfare state and the EU affect Europeans' family related choices.